Measuring Services Trade Liberalization and Its Impact on Economic Growth : An Illustration - Mattoo, Aaditya (World Bank, Washington, DC, 2014)
The authors explain how the output growth effect from liberalizing the service sectors differs from the effect from liberalizing trade in goods. They also suggest using a policy-based rather than outcome-based measure of the openness of a country's service regime. They construct such openness measures for two key service sectors' basic telecommunications and financial services. Finally, the authors provide some econometric evidence--relatively strong for the financial sector and less strong, but nevertheless statistically significant, for the telecommunications sector--that openness in services influences long-run growth performance. Their estimates suggest that growth rates in countries with fully open telecommunications and financial services sectors are up to 1.5 percentage points higher than those in other countries.